Implementation of Klungkung Regent Regulation Number 15 of 2020 Concerning Guidelines for Grants and Social Assistance in Klungkung Regency - Tirka Widanti, Ni Putu; Risna Supria Dewi, Luh (KnE Social Sciences, 2022)
This study examined how the Klungkung regent rule number 15 of 2020 about the guidelines for grants and social assistance in the Klungkung regency is being implemented. Barriers to implementation were identified and methods to overcome them were proposed. Effectiveness, efficiency, sufficiency, equality, responsiveness, and correctness were the six characteristics studied in the execution of the regulation. A descriptive qualitative approach was utilized. The data were obtained through structured interviews and observation. The findings showed that, notwithstanding a few roadblocks, the Klungkung regent regulation number 15 of 2020 regulating guidelines for grants and social assistance in the Klungkung district has been implemented successfully in the administration of grant requests. Keywords: grant, Klungkung regent regulation, policy implementation, social assistance